Genetic determinants of the phenotype in a Swedish cohort of patients with hypertrophic cardiomyopathy - Antheia, Kissopoulou; Eva, Fernlund ; 0000-0001-6508-9411; Jan-Erik, Karlsson; Henrik, Green; Rada, Ellegård; Cecilia, Gunnarsson (Scientific Reports, 2025)
Hypertrophic cardiomyopathy (HCM), the most common inherited cardiomyopathy, is characterized by phenotypic and genetic heterogeneity. The present study describes the genotype data of a Swedish cohort of patients with HCM, the largest genetics study on Swedish HCM patients to date. The primary aims of this study were to unravel the main genetic findings and explore genotype–phenotype associations in this HCM cohort. Longitudinal data on 225 unrelated HCM index patients from the Southeast health care region in Sweden from 2010 until 2021 were assessed retrospectively. Patients were 46 ± 15.5 years-old, 67.6% males. In the cohort, 172/225 (76.4%) had genetic testing, of whom, 65/172 (38%) were considered genotype positive (G +) for a pathogenic/ likely pathogenic variant, mainly in the two most common sarcomeric genes: MYBPC3 (57%) and MYH7 (34%). In 43% (74/172) of patients, no reportable variants were detected, classified as genotype negative (G-). In the remaining 33 patients (19%), variants of uncertain significance (VUS) were identified; this group was not included in the comparative analyses. Genotype positive patients (G +) were characterized by younger age (p = 0.010), higher prevalence of family history of HCM (p < 0.001), greater maximum left ventricle wall thickness (p = 0.03) and an increased incidence of sudden cardiac death (SCD) (p = 0.045). At first clinical screening, HCM was diagnosed in 28/65(43%) in the G + families and in 2/74 (2.7%) G-families (p < 0.001). Genotype-positive HCM patients differ with respect to age at presentation, family history of the disease, morphology, incidence of SCD and presence of HCM in their family members at first clinical assessment from genotype-negative patients. Genotype negative status in this HCM cohort, though, did not confer immunity from adverse complications.